Effect of Recombinant Human Soluble Thrombomodulin on Coagulation-Related Variables in Patients With Sepsis-Induced Disseminated Intravascular Coagulation: A Retrospective Observational Study - Chieko Mitaka (SAGE Publishing, 2021)
To evaluate associations among coagulation-related variables, resolution of disseminated intravascular coagulation (DIC) and mortality, we retrospectively investigated 123 patients with sepsis-induced DIC treated with recombinant human soluble thrombomodulin (rTM). Changes in coagulation-related variables before and after treatment with rTM were examined. Further, associations between coagulation-related variables and DIC resolution were evaluated. The platelet count, prothrombin international normalized ratio (PT-INR), and fibrin/fibrinogen degradation products (FDP) significantly ( p  < .001) improved after rTM administration in survivors (n = 98), but not in nonsurvivors (n = 25). However, the DIC score significantly ( p  < .001) reduced in survivors and in nonsurvivors. Among coagulation-related variables examined before rTM, only PT-INR was significantly ( p  = .0395) lower in survivors than in nonsurvivors, and PT-INR before rTM was significantly ( p  = .0029) lower in patients attaining than not attaining DIC resolution (n = 87 and 36, respectively). The 28-day mortality was significantly lower in patients attaining than not attaining DIC resolution (11.5% vs 41.7%, p  = .0001). In conclusion, the initiation of rTM administration before marked PT-INR elevation may be important to induce DIC resolution and thus to decrease mortality in patients with sepsis-induced DIC. Conversely, the treatment with rTM in patients with marked PT-INR elevation may be not so effective in achieving such goals.